Quality of life and mental health of children with rare congenital surgical diseases and their parents during the COVID-19 pandemic - Fürböter, Mareike; Boettcher, Johannes; Barkmann, Claus; Zapf, Holger; Nazarian, Rojin; Wiegand-Grefe, Silke; Reinshagen, Konrad; Boettcher, Michael (Orphanet journal of rare diseases, 2021)
Background:  COVID-19 has affected our society at large, particularly vulnerable groups, such as children suffer‑ing from rare diseases and their parents. However, the psychosocial influences of COVID-19 on these have yet to be investigated. As such, the study’s goal was to evaluate the health-related quality of life (HRQoL), quality of life (QoL), and mental health of children with rare congenital surgical diseases and their parents during the COVID-19 pandemic and lockdown measures. - Methods:  A survey of n = 210 parents of children with rare congenital surgical diseases and a control group of n = 88 parents of children without rare diseases was conducted cross-sectionally between April 2020 to April 2021. Data on HRQoL, QoL, and mental health was collected using standardized psychometric questionnaires for children and parents presenting to the pediatric surgery department at a university hospital. - Results:  Mothers of children with rare pediatric surgical diseases showed significantly lower QoL and significantly higher impairment in mental health than a control group and norm data. For fathers, this was solely the case for their QoL. Children’s parent-reported HRQoL and mental health were partially impaired. Social and disease-specific risk fac‑tors of the respective outcomes in affected families were identified through regression analysis models. - Conclusion:  Parents of children with rare diseases report severe psychosocial impairment regarding themselves and their children during the COVID-19 pandemic. Therefore, affected families should receive attention and supportive care in the form of a family-center approach to alleviate the additional burden of the COVID-19 pandemic.